The Role of the Energy Community Within the EU Regional Cooperation - Victoria Musteata (CES Working Papers, 2012)
In the last decade we have seen the creation process of a common Energy Policy, which was gradually adopted by all Community countries, and has promoted an integrated competitive European energy market, increased security of supply and supported the use renewable energy sources. But in order for this policy to work efficiently, it also had to promote international cooperation with its neighbors and energy suppliers. With the view of establishing an Integrated Energy Market Organization in South-Eastern Europe, the European Community, along with nine other countries, has signed on 25 October 2005 the treaty establishing the Energy Community. Our research aims to investigate the potential of the European Union to promote security of energy supply and energy markets integration through the Energy Community. The article uses data from theoretical and empirical research on the economic and politic relations between the members of the Energy Community in order to establish the positive and negative outcomes of six year of collaboration.
Keywords: F15; F59; N74; O19; O31; 330; European Energy Community; EU energy policy; EU external relations; market integration; Europeanization; Regional integration; Neo-functionalism; Stability Pact for South East Europe Romania